Frumusețea slujbelor bisericești în sufletul tânărului de azi - Stanciu, Vasile (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
Young people are the same, in any period of history, with their intentions, their aspirations, their ideals, their age-specific concerns, their problems, their failures and their successes. The Church, through its voice, which is the voice of Christ, can offer the perspective of a spirituality in which today’s young people can find themselves. And one of the coordinates of this spirituality is precisely the Church service, which he listens to and participates in. An important, essential role is played by the musical component of church services. Liturgical music has its own theology, in which two components are combined: the hymn text and the melody. Church services are the soul that animates the entire life of the Christian, of today’s youth. They are like spiritual food without which we cannot conceive an authentic and personal, but also communal relationship with God.